Political Defection in Nigeria: An Approach to Political Power-Based Theory - Ibrahim, Amadu (Kashere Journal of Politics and International Relations, 2023)
Political defections in Nigeria have become a commonplace especially in the Fourth Republic. Elected or appointed public officials find it attractive to defect from one political party to another in search of political power. The literature on political defection in the country generally emphasises on the causes of political defections, rather than on how the defection occurs or what their effects might be on the democratic system. Thus, the aim of this study is to develop a theory to explain how political defections occur. The theory, based on the available evidence, shows that defection effect syndrome has the capacity of altering the balance of power among political parties; and in order to do that, it must reach a certain critical mass. In addition, the theory indicates that the effects of a political defection or a defection effect syndrome on the various elements of the democratic system depend on the nature of political support base of the defectors which may be either an elite-supported political base or a voter-supported political base or both. In all, the effects of defection effect syndrome include altering the party system or influencing the outcomes of the elections.